The impact of low interest rates on the debt of polish listed companies - Schmidt, Katarzyna (Research Papers in Economics and Finance, 2019)
Central bank decisions have an impact on the whole economy. Increasing or lowering interest rates as part of a specific policy determines not only changes in macroeconomic aggregates or decisions of financial entities, such as banks, but also has a significant impact on business decisions. Low interest rates, which have been maintained for several years, encourage reflection on the impact of interest rates on the financing structure of companies. The main objective of the research is to verify the relations between monetary policy, in particular low interest rates, and the level of indebtedness of Polish listed companies. The analysis showed that the level of total interest-bearing liabilities for the selected sample of companies remains in a clear upward trend, and interest rates – in a downward trend, excluding the increases in 2008 and 2012. The Pearson correlation for the variables in question should be considered strong, especially in the case of the relationship between long-term interest-bearing liabilities and interest rates. Considering the above, it should be noted that interest rates influence the level of indebtedness of companies, bearing in mind that this is a transmission channel of monetary policy, which operates with a time lag.